(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To evaluate the effectiveness of low-level Laser therapy in rapid palatal expansion in treatment of patients with posterior crossbite and assess the affect of Laser settings to effectiveness of the expansion. Methods: A systematic review conducted on electronic databases PubMed, Cochrane Library and Embase. Output parameters of interest include the expansion of midpalatal suture, change in optical density of mid-palatal suture and the change in maxilla width. Results: There are a total of 8 studies that performed low-level Laser therapy with rapid maxillary expansion to treat posterior crossbite. All studies reported that low-level Laser therapy was effective in rapid maxillary expansion with reports of an average increase in the horizontal dimension of the maxilla from 2.7 mm ± 2.32 mm to 3.24 mm ± 2.67 mm, an increase in mid-palate suture width and in the optical density of the mid-palate suture in both the Laser and Non-Laser groups. Factors such as wavelength, power, energy density, Laser exposure time and position do not affect the expansion result. Conclusion: Low-level Laser therapy is effective in rapid maxillary expansion in treatment of patients with posterior crossbites.